Analisis Praktik Klinik Keperawatan pada Pasien Stroke Hemoragik dengan Terapi Inovasi Mobilisasi (Rom Pasif) dan Rangsangan Taktil Terhadap Pemulihan Anggota Gerak Atas di Ruang Hcu Rsud Prof. Dr. H. Aloei Saboe Kota Gorontalo - Fadli Syamsuddin; Meyske Y. Yasin (Jurnal Rumpun Ilmu Kesehatan, 2023)
Background: Stroke is one of the main health problems for the community because stroke can cause damage to the brain that appears suddenly, progressively, and quickly due to non-traumatic brain blood circulation disorders. Purpose: To conduct an analysis of managed cases with a medical diagnosis of hemorrhagic stroke with innovative mobilization therapy (Passive ROM) and tactile stimulation for upper limb recovery in the HCU Room of Prof. Dr. H. Aloei Saboe City of Gorontalo Methods: This research is a quasi-experimental design with pre and post test. To determine the effect of providing innovative mobilization therapy (Passive ROM) and tactile stimulation to hemorrhagic stroke patients in the HCU Room of Prof. Dr. H. Aloei Saboe City of Gorontalo. The sample used in this study were 5 patients with the sample criteria being patients who had hemorrhagic strokes who were treated in the HCU Room at Prof. Hospital. Dr. H. Aloei Saboe Gorontalo City, patients who experience hemiparesa, patients have awareness of compos mentis. Results: Implementation of innovation in Mrs.FK On the first day the Ara test score was 0 until the third day there was no increase in the Ara test value which was still 0. Mr. RA on the first day the Ara test value was 1, on the third day the Ara test value increased enough to be 2. On Mr. UT on the first day the Ara test value was 0, on the third day the Ara Test value was 1. Mr. AH on the first day the Ara test value was 0, on the third day the Ara Test value was still 0. Mr. MH on the first day the Ara test value was 1, on the third day the Ara Test value increased to 2. Conclusion: Based on the research conducted, it was found that 5 respondents from the results of the study had the same complaint, namely experiencing weakness/hemiparesis of the upper extremities. The client's upper extremity muscle strength is 1/5, 3/4, 2/4, 4/2, 4/5, when the motor function test is carried out by holding the researcher's hand the client is unable to grip,